Anterior Opening Wedge High Tibial Osteotomy for Recurvatum Deformity of the Proximal Tibia Secondary to Physeal Arrest: A Dual Site Study - John J. Bartoletta; Gregory A. Schmale; Tressa M. Mattioli-Lewis; Maryse Bouchard (Journal of Limb Lengthening & Reconstruction)
Context: Injury to the anterior proximal tibial physis or tibial tubercle can result in recurvatum deformity of the tibia. Anterior opening wedge high tibial osteotomy (AHTO) with and without tibial tubercle osteotomy (TTO) can restore posterior tibial slope, improving patient symptoms and function. Aims: Review radiographic and surgical outcomes of patients that undergo AHTO for recurvatum deformity of the proximal tibia. Settings and Design: Patients from two tertiary pediatric institutions with proximal tibial recurvatum treated with an AHTO between 2002 and 2017 were retrospectively reviewed. Materials and Methods: Deformity was assessed radiographically using the posterior proximal tibial angle (PPTA), medial proximal tibial angle, and Caton–Deschamps index (CDI). Surgical techniques and complications were recorded. Statistical Analysis Used: Descriptive statistics were expressed as means and standard deviations. Results: Twelve patients with a mean age of 13.1 years (10–15 years) were included in this study. Acute AHTO proximal to the tibial tubercle was performed in nine cases. Two patients had concurrent TTO. Three patients underwent AHTO with gradual correction with a Circular external fixator with the corticotomy distal to the tibial tubercle. Mean postsurgical follow-up was 6.1 months (1.3–15.6 months). Mean preoperative PPTA improved to within normal for all surgical techniques (AHTO 98.7° to 82.6°, AHTO + TTO 102° to 80.9°, and gradual AHTO 104° to 76.9°). Three patients had residual radiographic hyperextension deformity at last follow-up (PPTA: 85.0°, 87.9°, 94.0°). No clinically significant secondary coronal plane deformities occurred. One patient who underwent acute AHTO had postoperative radiographic patella baja (CDI 0.51). Ten complications (7 Grade I and 3 Grade II) occurred in seven cases. Conclusions: Opening wedge AHTO with acute and gradual techniques corrects the sagittal plane deformity of recurvatum without inducing clinically significant coronal plane deformities, but minor complications are frequent.